Cytokinins: A key player in determining differences in patterns of canopy senescence in Stay-Green and Fast Dry-Down sunflower (Helianthus annuus L.) hybrids - Mangieri, Mariano Alejandro (2017)
Leaf senescence during grain filling can reduce crop yield. We studied, under field conditions and during grain-filling, the association between leaf cytokinin levels and the onset of leaf senescence in sunflower hybrids of contrasting canopy senescence patterns (Paraiso75, stay-green [SG] and Paraiso65, fast dry down [FDD]). At crop level, dynamics of live root length density (LRLD) and green leaf area index (GLAI) were followed, while at leaf level dynamics of total chlorophyll content, trans-Zeatin content, net photosynthesis and PSII quantum yield, were followed in leaf positions 17, 20, 22 and 24. Responses of these leaf variables to exogenous cytokinin applications to leaves at position 17 were also followed. SG exhibited greater (p < 0.05) LRLD and GLAI values at anthesis. In both hybrids, LRLD began to fall before GLAI. All variables decreased earlier (p < 0.05) in FDD. Initial leaf levels of trans-Zeatin were three times higher (p < 0.05) in SG. Exogenous cytokinin applications maintained leaf-level variables. These are the first results showing associations between LRLD dynamics with the dynamics of leaf cytokinin levels and changes in indicators of leaf functionality. Also, this is the first study in which estimates are made of cytokinin thresholds below which leaf senescence begins in two hybrids of contrasting canopy senescence patterns. These advances in the understanding, at both crop and leaf levels, of the controls and consequences of SG during grain filling, a trait known to improve crop water uptake under drought and increase biomass accumulation during grain filling, provide support for breeding efforts aimed at profiting from this trait to increase crop yields.